Investment in intellectual capital and achievement of the competitive advantage in hotel sector - Qasim Mohammed Dahash; Ammar Nazar Mustafa Al-Dirawi (Management Science Letters, 2018)
The primary objective of the research paper is to provide some insights on the concepts of intellec-tual capital and its important dimensions alongside to investigate the possible association between intellectual capital and attainment of competitive advantage. This study focuses on Iraqi hotel industry which is an under-research area in the context of intellectual capital and its relationship with competitive advantage. An adapted questionnaire was utilized to collect the responses from top and middle level managers of four and five-star hotels in Iraq. The reliability and validity of data collec-tion instrument were measured through Cronbach’s alpha, Composite Reliability and Average Var-iance Extracted respectively. The competitive advantage was then regressed against Human, Rela-tional and Structural capital by application of Partial Least Square methodology. Results of the study showed a positive and strong connotation among intellectual capital and attainment of competitive advantage. The human capital had the highest contribution for competitive advantage in hotel sector of Iraq. The top management of hotels should take interest to develop, maintain and retain human capital to attain competitive advantage over competitors.